Different assessment instruments in Morphophysiology - Cecho, Analía Cristina (2008)
Assessment is a quality control system that determines the efficacy of the teaching process. As teachers of the School of Dentistry, we consider only one or two summative evaluations insufficient as controls for learning. For this purpose, we implemented daily assessment mechanisms using different instruments. The selected instruments were: 1) open book synthesis: emphasizing problem solving; 2) open questions: clear and precise interrogates; 3) conceptual maps: the concepts should be hierarchically related with an inner coherence; 4) multiple choice test (type I and II): the student should choose one answer from several options; 5) puzzles (type I and II), designed for stimulation of intellectual, sensorial and affective areas; 6) fill in the blanks sentences: principles, norms, regulations or statements where the main words have been deleted and the blank left to be properly fulfilled; 7) matching test: two series of data are presented and the student should match those that correspond; and 8) multiple election test.